2000
DOI: 10.1111/j.1346-8138.2000.tb02174.x
|View full text |Cite
|
Sign up to set email alerts
|

The Bacteriology of Acne Vulgaris and Antimicrobial Susceptibility of Propionibacterium acnes and Staphylococcus epidermidis Isolated from Acne Lesions

Abstract: We examined the species of bacteria aerobically and anaerobically isolated from 30 acne lesions and determined antimicrobial susceptibilities of Propionibacterium acnes (P. acnes) and Staphylococcus epidermidis (S. epidermidis) using nine antimicrobial agents. Among the bacteria isolated, S. epidermidis was most dominant. Both P. acnes and S. epidermidis were isolated from half of the acne lesions. The MIC of seven antimicrobials (ampicillin, erythromycin, roxithromycin, clindamycin, tetracycline, minocycline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 13 publications
(13 reference statements)
4
71
1
3
Order By: Relevance
“…Previous studies have also reported resistance of coagulasenegative staphylococci and S. aureus against clindamycin and erythromycin. 9,10,25) Our results indicated that the isolates from the antibiotic-treated subjects were less susceptible to clindamycin and erythromycin (commonly used topical antibiotics for acne treatment) than those from the untreated subjects. Similar reports were also documented.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Previous studies have also reported resistance of coagulasenegative staphylococci and S. aureus against clindamycin and erythromycin. 9,10,25) Our results indicated that the isolates from the antibiotic-treated subjects were less susceptible to clindamycin and erythromycin (commonly used topical antibiotics for acne treatment) than those from the untreated subjects. Similar reports were also documented.…”
Section: Discussionmentioning
confidence: 63%
“…10,23,24) In the present study, the resistance of staphylococci was found in most groups of antibiotics, especially clindamycin, erythromycin, and penicillin. Previous studies have also reported resistance of coagulasenegative staphylococci and S. aureus against clindamycin and erythromycin.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…[9] Staphylococcus epidermidis was the predominant aerobic bacterial isolates & Propionibacterium acnes was the predominant anaerobic bacterial isolates in the present study and also in other studies (Table 8 & 9). [9,10] In the study by Parvin Hassanzadeh et al, the most frequent bacteria isolated from acne patients were Staphylococcus aureus & it was stated that it is possible that acne vulgaris is mainly caused by Staphylococcus aureus rather than Propionibacterium acne. This is in contrast to reports which implicated both Staphylococcus epidermidis and Propionibacterium acnes as bacteria causing acne vulgaris.…”
Section: Discussionmentioning
confidence: 99%
“…and the prevailing finding is Propionibacteium acnes. This strain is typical by the production of catalase and indol 2,15,29 . For the determination of staphylococci, the material is inoculated on agar soil (e.g.…”
Section: Diagnostics Of Acnementioning
confidence: 99%